Structural organization and functional analysis of centromeric DNA in the fission yeast Schizosaccharomyces pombe. - Fishel, B (1988)
Centromeric DNA in the fission yeast Schizosaccharomyces pombe was isolated by chromosome walking and by field inversion gel electrophoretic fractionation of large genomic DNA restriction fragments. The centromere regions of the three chromosomes were contained on three SalI fragments (120 kilobases [kb], chromosome III; 90 kb, chromosome II; and 50 kb, chromosome I). Each fragment contained several repetitive DNA sequences, including repeat K (6.4 kb), repeat L (6.0 kb), and repeat B, that occurred only in the three centromere regions. On chromosome II, these repeats were organized into a 35-kb inverted repeat that included one copy of K and L in each arm of the repeat. Site-directed integration of a plasmid containing the yeast LEU2 gene into K repeats at each of the centromeres or integration of an intact K repeat into a chromosome arm had no effect on mitotic or meiotic centromere function. The centromeric repeat sequences were not transcribed and possessed many of the properties of constitutive heterochromatin. Thus, S. pombe is an excellent model system for studies on the role of repetitive sequence elements in centromere function.